Іван Новак – один із тисяч українців, розстріляних у період «великого терору» - Міщанин, В. (Сiверянський лiтопис, 2018)
У статті, на основі архівно-кримінальної справи, висвітлена трагічна доля Івана Гнатовича Новака, розстріляного навесні 1938 року за постановою особливої трійки УНКВС по Полтавській області. На момент арешту він працював пропагандистом Зіньківського райкому КП(б)У в Полтавській області. Перебував у родинних стосунках із Дмитром Біликом – колишнім директором гончарної школи в Опішному та колишнім лівим есером. В статье, на основании материалов архивно-уголовного дела, рассказывается о трагической судьбе Ивана Игнатьевича Новака, расстрелянного весной 1938 года по постановлению особой тройки УНКВД по Полтавской области. На момент ареста он работал пропагандистом Зеньковского райкома КП(б)У в Полтавской области. Был в родственных связях с Дмитрием Билыком – бывшим директором гончарной школы в Опишному и бывшим левым эсером. The article based on the archival criminal case shows the tragic fate of Ivan Novak shot in spring, 1938, according to the decision of the NKVD institutional commission in the Poltava region. At the time of his arrest he worked as a propagandist of the Zinkiv district committee of the Communist Party in the Poltava region. On the basis of fabricated evidence Ivan Novak was accused of belonging to the actually non-existent Ukrainian nationalist organization. Ivan Novak was exonerated on the 13th of June, 1958. But they did not inform his family about the truth of his fate. His younger daughter, Lina, learned the truth about her father only in 2017 from the article’s author, after his studying the archival criminal case. Ivan Novak was married to Yevdokiia Bilyk from Opishne. She was a sister of Dmytro Bilyk, a former director of the Opishne pottery school, a former left social revolutionary. Dmytro Bilyk was also repressed in the late 1930s.